SOME ASPECTS OF TEACHING THE TRANSPORTATION PROCESS IN TRANSPORT TECHNOLOGIES - Slavych , Viacheslav; Slavych , Anna; Elnyk , Vadym (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2023)
The article deals with the method of training future specialists in the transport industry in the skills and abilities of the process of optimizing freight transport routes using the example of an enterprise The new route turned out to be optimal under the specified conditions and economically profitable.